Influência da água de entrada sobre as variáveis bióticas e abióticas em um viveiro de piscicultura - Sipaúba-Tavares, L. H. [UNESP]; Durigan, P. A. [UNESP]; Berchielli-Morais, F. A. [UNESP]; Millan, R. N. (FapUNIFESP (SciELO), 2017)
The effects of treated and untreated water inlets with macrophytes on the improvement of water quality and zooplankton community were evaluated in a fish pond with continuous water flow. Water and zooplankton samples were retrieved at four sites during nine months. There were differences (p<0.01) between inlet water from fish pond and inlet water from canal with macrophytes, featuring higher concentrations of nutrient load, mainly TAN and TP in the former. The inlet water from fish pond contained a higher number of abundant species (9 species), whilst the water supply from the canal with macrophytes had a greater richness (31 species) of zooplankton species. Results showed that inlet water without macrophytes directly affected the characteristics of the water column and the dominance of zooplankton species such as Thermocyclops decipiens, and greater abundance of Rotifera species. Since aquatic plants in the inlet water of fish pond analyzed showed lower allochthonous material loads from the previous fish pond, the management adopted with macrophytes may be applied to avoid eutrophication risks, common in farm ponds.
Influence of inlet water on the biotic and abiotic variables in a fish pond
Keywords: Continuous water flow; Macrophytes; Management; Zooplankton